2019
DOI: 10.1159/000503218
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Complications after Skin-Sparing and Nipple-Sparing Mastectomy

Abstract: Introduction: In order to achieve a complication-free breast reconstruction, it is fundamental for each individual patient case to determine preoperatively certain risk factors that might have a negative impact on the postoperative result after skin-sparing (SSM) or nipple-sparing mastectomy (NSM). Methods: A retrospective study of 39 female breast cancer patients who received SSM or NSM breast reconstruction in our department (time interval: 2010–2015), was performed. The study focus is on determining patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Surgical incision options and surgical types should be evaluated based on the tumor situation and patient needs. [ 18 ] This study showed that different surgical types ( P = 0.154) and surgical incisions ( P = 0.098) did not relate to the postoperative complication rate. Restricted by strict indications, NSM is recommended more to patients with a poor expected outcome of breast-conserving surgery (smaller breasts, negative surgical margins cannot be achieved by breast-conserving surgery).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Surgical incision options and surgical types should be evaluated based on the tumor situation and patient needs. [ 18 ] This study showed that different surgical types ( P = 0.154) and surgical incisions ( P = 0.098) did not relate to the postoperative complication rate. Restricted by strict indications, NSM is recommended more to patients with a poor expected outcome of breast-conserving surgery (smaller breasts, negative surgical margins cannot be achieved by breast-conserving surgery).…”
Section: Discussionmentioning
confidence: 81%
“…Most studies have shown that the incidence of NAC involvement was significantly associated with tumor size. [ 7 , 18 ] Some studies suggested that NSM can be performed safely regardless of tumor size, as long as the deep nipple and areola area had negative surgical margins. [ 19 ] With a threshold tumor diameter of 2 cm, tumor size did not significantly relate to the rates of postoperative complications, recurrence, and metastasis after NSM.…”
Section: Discussionmentioning
confidence: 99%
“…Patient characteristics such as smoking history, prior radiation, increasing BMI, and large ptotic breasts have demonstrated an increased risk. 11 12 Given that radiotherapy is recommended in more advanced cancers or those with high-grade features, that may also result in a greater risk of nipple necrosis. However, this was not the case for either of our patients who were diagnosed with low-grade in situ cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The operation is not morbid as the rate of mastectomy complications is nearly as reported by other studies describing pure mastectomy. 17,18 The incidence of epigastric hernia is low, and this complication can be avoided by proper tunnel closure. The incidence of partial breast envelop ischemia was 5.4%, and this was exclusively met with the inframammary incision due to the longer flap.…”
Section: Discussionmentioning
confidence: 99%